Insecticidal activity of Annona muricata (Anonaceae) seed extracts on Sitophilus zeamais (Coleoptera: Curculionidae) - HINCAPIÉ-LLANOS, CARLOS AUGUSTO; LOPERA-ARANGO, DAVID; CEBALLOS-GIRALDO, MARILUZ (Revista Colombiana de Entomología, 2008)
The corn weevil Sitophilus zeamais is a very significant pest worldwide that causes severe damage to stored grains resulting in high economic losses. In the present study, the insecticidal effect of Annona muricata (soursop) seed extracts was evaluated. The extracts were obtained using hexane (non polar), ethyl acetate (half polar) and ethanol (polar), and these were applied to S. zeamais adults using ingestion and topical application. The emergence of new adults in corn seeds treated with the extracts was also evaluated. The LC50 (median lethal concentration) obtained in the ingestion bioassays for the hexane extract was 4,009, 3,854 and 3,760 ppm at 24, 48 and 72 hours, respectively. For the ethyl acetate extract it was 3,280, 2,667 and 2,542 ppm at the same times. The LC50  of the hexane extract in the topical application was 9,368 ppm at 72 hours. The other extracts in both bioassays showed little insecticidal activity. Emergence was 100% inhibited at concentrations of 2,500 ppm for the ethyl acetate and hexane extracts and at 5,000 for the ethanol extract. The insecticidal effect of the ethanol extracts is debatable given their low efficacy. The extracts are more effective through ingestion than by contact. The insecticidal effect is probably caused by the presence of acetogenins in the less polar fractions of the A. muricata seeds.